Coping strategies for domestic violence: Testimony of women involved with drugs - Milca Ramaiane da Silva Carvalho; Jeane Freitas de Oliveira; Nadirlene Pereira Gomes; Luana Moura Campos; Lilian Conceição Guimarães de Almeida; Luana Rodrigues Santos (Universidade Federal do Rio de Janeiro, 2019)
ABSTRACT Objective: To understand strategies used by women involved with alcohol and/or other drugs to cope with domestic violence. Methods: A qualitative study using the theoretical framework of coping strategies proposed by Folkman and Lazarus. 19 women with reports of domestic violence and involvement with alcohol and/or other drugs attended to at Family Health Units in a city of Bahia, Brazil. The data were systematized based on Discourse of the Collective Subject. Results: Given the context of domestic violence and drug use, women confront their partners; they try to have a conversation; they seek family and institutional support and take responsibility and blame for the aggression suffered. Conclusions and implications for practice: The strategies listed may support actions to prevent and cope with the phenomenon, especially from the intersectoral articulation.